Pembinaan Keislaman Mualaf Pedalaman: Kolaborasi Kuliah Kerja Nyata Internasional dan Pusat Dakwah Islamiah Brunei Darussalam: Indonesia - Adawiyah, Choirun; muhammad, muhammad doktor; afandi, agus (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
This community service aims to describe efforts to strengthen Islamic understanding among Muslim converts (muallaf) in remote areas of Brunei Darussalam through international collaboration between KKN students from UIN Sunan Ampel Surabaya and Pusat Dakwah Islamiah (PDI) Brunei Darussalam. Muallaf communities in long houses face significant limitations in their understanding and practice of Islam due to geographical isolation, minimal access to Islamic education, and lack of continuous post-conversion mentoring. The implementation method uses an Asset-Based Community Development (ABCD) approach with learning by doing and participatory techniques. Data collection was conducted through direct observation, activity documentation, and reflective field notes during the mentoring process. Activities were carried out in Kampung Semabat-Temburong, Kampung Sungai Mao-Belait, and Kampung Bebuloh-Muara through direct visits, guidance on basic worship practices (ablution, prayer, daily supplications), interactive religious dialogue, and provision of social assistance. Results showed that before the activity, muallaf had limited Islamic understanding in worship practices and mastery of prayer recitations. After intensive mentoring, significant improvements occurred with participation rates reaching 85% and more than 80% of participants able to perform ablution and prayer independently, better understand Islamic teachings, and develop stronger religious spirit. Social impacts include the formation of regular religious gatherings, increased self-confidence among muallaf, and harmonization of interfaith relations. This program confirms the important role of KKN International students and PDI in accompanying and strengthening the spirituality of muallaf to be more steadfast in practicing Islamic teachings in daily life.